2007
DOI: 10.1021/ie0709685
|View full text |Cite
|
Sign up to set email alerts
|

Ether-Functionalized Imidazolium Hexafluorophosphate Ionic Liquids for Improved Water Miscibilities

Abstract: The hexafluorophosphate anion of 1-alkyl-3-methylimidazolium ionic liquids is responsible for their poor water miscibility. Transformation of the hexafluorophosphate ionic liquids into water miscible liquids by structural modifications in the imidazolium cation could result in new applications. Improved water miscibilities were achieved with 1-alkyl ether-3-methylimidazolium hexafluorophosphate ionic liquids. Especially, ionic liquid 1-triethylene glycol monomethyl ether-3-methylimidazolium hexafluorophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…For example, 1-(2-hydroxypropyl)-3-methylimidazolium based ILs (paired with various anions such as Cl − , NO 3 − , PF 6 − and Tf 2 N − ) are more hygroscopic and more miscible with water than the alkyl-substituted analogues. 75 Schrekker et al 139 observed that the incorporation of an ether chain into the imidazolium cation greatly improves hydrophilicity and water miscibility of PF 6 − based ILs; the hydrophilicity increases in the order of [BMIM][PF 6 ] < [MeO(CH 2 ) 2 -MIM][PF 6 ] < [Me(OCH 2 CH 2 ) 3 -MIM][PF 6 ], and at 50 °C the latter is completely miscible with water. A dimethylammonium-based IL containing two PEG-350 methyl ether chains is completely miscible with water due to the hydrophilic nature of the two long alkoxy chains 59 while 1-(2-hydroxyethyl)-3-methylimidazolium hexafluorophosphate ([(HOCH 2 CH 2 )-MIM][PF 6 ]), is soluble in water at >50 kg m –3 at 25 °C.…”
Section: Physicochemical Properties Of Ether- and Hydroxyl-functiomentioning
confidence: 99%
“…For example, 1-(2-hydroxypropyl)-3-methylimidazolium based ILs (paired with various anions such as Cl − , NO 3 − , PF 6 − and Tf 2 N − ) are more hygroscopic and more miscible with water than the alkyl-substituted analogues. 75 Schrekker et al 139 observed that the incorporation of an ether chain into the imidazolium cation greatly improves hydrophilicity and water miscibility of PF 6 − based ILs; the hydrophilicity increases in the order of [BMIM][PF 6 ] < [MeO(CH 2 ) 2 -MIM][PF 6 ] < [Me(OCH 2 CH 2 ) 3 -MIM][PF 6 ], and at 50 °C the latter is completely miscible with water. A dimethylammonium-based IL containing two PEG-350 methyl ether chains is completely miscible with water due to the hydrophilic nature of the two long alkoxy chains 59 while 1-(2-hydroxyethyl)-3-methylimidazolium hexafluorophosphate ([(HOCH 2 CH 2 )-MIM][PF 6 ]), is soluble in water at >50 kg m –3 at 25 °C.…”
Section: Physicochemical Properties Of Ether- and Hydroxyl-functiomentioning
confidence: 99%
“…[21][22][23] These functionalized ILs increased water solubility compared to their alkyl-derivatized counterparts. 24 The potential of such ILs in gas separations has been recently reported with polymer gas separation membranes based on polymerizable etherderivatized ILs. 25 No thermodynamic property of cyanoalkyl-substituted ILs was found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to conventional volatile organic compounds (VOCs), most ILs are generally regarded as "green" solvents due to their immensely low vapor pressure [4]. The class of imidazolium cation-based RTILs has been demonstrated to be highly attractive in extraction and separation processes because their structural modifications in both the cation (especially the 1 and 3 positions of the imidazolium ring) and anion permit the tuning of properties such as miscibility with water and organic solvents, the melting point and viscosity [2]. Effort has been made with imidazolium ionic liquids as extraction solvents in liquid phase microextraction (LPME).…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature ionic liquids (RTILs) are a special class of ionic liquids (ILs) with the melting point at or below 25 °C [1][2][3]. Contrary to conventional volatile organic compounds (VOCs), most ILs are generally regarded as "green" solvents due to their immensely low vapor pressure [4].…”
Section: Introductionmentioning
confidence: 99%